2005
DOI: 10.1097/01.fpc.0000167330.92786.5e
|View full text |Cite
|
Sign up to set email alerts
|

Significance of a common single nucleotide polymorphism in exon 10 of the follicle-stimulating hormone (FSH) receptor gene for the ovarian response to FSH: a pharmacogenetic approach to controlled ovarian hyperstimulation

Abstract: The p.N680S sequence variation of the follicle-stimulating hormone (FSH) receptor gene was previously shown to influence the ovarian response to FSH in normo-ovulatory women undergoing controlled ovarian hyperstimulation. In this prospective, randomized, controlled study, we tested whether the same daily dose of FSH results in lower levels of oestradiol in women homozygous for the p.N680S sequence variation, and whether the difference can be overcome by higher FSH doses. Women undergoing controlled ovarian hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
117
6
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(134 citation statements)
references
References 13 publications
7
117
6
4
Order By: Relevance
“…G −29 A, A 919 G (Thr 307 Ala) and A 2039 G (Asn 680 Ser) polymorphisms have been extensively studied by different investigators. It was reported that the polymorphism A 2039 G is associated with high basal FSH levels in women undergoing Assisted Reproductive Technology (ART) programme [17][18][19][20][21][22]. Recently, we have reported association of FSHR gene polymorphism (A 919 G, G −29 A) with altered ovarian response in subjects undergoing gonadotropin treatment during ART programme [23,24].…”
Section: Introductionmentioning
confidence: 94%
“…G −29 A, A 919 G (Thr 307 Ala) and A 2039 G (Asn 680 Ser) polymorphisms have been extensively studied by different investigators. It was reported that the polymorphism A 2039 G is associated with high basal FSH levels in women undergoing Assisted Reproductive Technology (ART) programme [17][18][19][20][21][22]. Recently, we have reported association of FSHR gene polymorphism (A 919 G, G −29 A) with altered ovarian response in subjects undergoing gonadotropin treatment during ART programme [23,24].…”
Section: Introductionmentioning
confidence: 94%
“…As the polymorphisms Thr307Ala and Asn680Ser are in linkage disequilibrium [3,18,19] the genotype of the FSHR 307 assays should in theory match the genotype of the FSHR 680 assays. Thus, the samples with limited samples material were analysed for minimum one of the two polymorphisms for each genotyping method, except for sample 22 in which all sample material was used for CADMA-based-and sequencing analysis.…”
Section: Analytical Sensitivity Of the Cadma-based Genotyping Assaysmentioning
confidence: 99%
“…Recently, a number of studies have shown that genetic polymorphisms of the gonadotropins and their receptors may affect the outcome of COS [2][3][4][5][6]. Especially the common polymorphisms of the FSH receptor (FSHR), rs6165 (c.919A > G, p. Thr307Ala, FSHR 307) and rs6166 (c.2039A>G, p. Asn680Ser, FSHR 680), has been shown to influence the sensitivity to exogenous FSH administration and the number of follicles recruited [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the majority of the studies, the presence of G/G was linked to a reduced sensitivity to exogenous FSH. This was demonstrated by a higher total dose of gonadotropins used during ovarian stimulation for IVF [5,6,9,11], a lower peak of estradiol levels on the day of hCG administration [6,19], a lower number of retrieved oocytes [11,15], and a higher incidence of the G/G variant in hypo-responder patients [20]. Furthermore, in a small study conducted with 37 patients, the A/A (Asn/Asn) variant was correlated to the severity of ovarian hyperstimulation syndrome (OHSS) [21].…”
Section: Introductionmentioning
confidence: 99%